Phased European Union electricity market reform - Georg Zachmann; Conall Heussaff (Bruegel, 2023)
In an environment of record-breaking electricity prices driven by a gas supply shock and below-average electricity generation, reforming the design of the European electricity market is seen as a means to delink consumer costs from volatility in short-term power markets. Electricity markets should meet three objectives: fairness, optimal investment and optimal operation. The current market design has achieved these objectives to varying degrees. Faced with the unprecedented shock, the electricity system has operated well, but electricity markets have struggled to achieve fair outcomes and investments have not been driven by market-based cashflows. Further complicating market reform, the power system is being changed radically by decarbonisation. The electricity system is becoming more decentralised and digitalised, with an active demand side. These transformations will have consequences for the optimal electricity market design in the later stages of the energy transition. Reform proposals have focused on increasing the share of long-term contracts in the remuneration of generation technologies. Different long-term contracting regimes have structural implications for the functioning of electricity markets, especially in relation to the roles of the state and the market, and the responsibilities of national governments and European Union institutions. A phased approach should be taken to EU electricity market design reform. In the near-term, reform should seek to protect consumers and drive investment. An assessment should also be made of what market design will best meet the fairness, investment and operational objectives in a decarbonised system, and what the conceptual role of electricity markets should be during the transition. This process should start as soon as possible so well thought-through proposals are available when the next European Commission takes office.
Keywords: 330